The Relationship between Metacognitive Strategy and Reading Comprehension at The Tenth Grade of Sman 3 Kabupaten Tangerang in Academic Year 2019/2020 - Hurriyah, Ika Rosiyatul; Nirmala, Nirna (Foremost Journal, 2020)
This article presents the analysis of metacognitive strategy and reading comprehension. The result shows that there is not any positive relationship between these variables. Although the metacognitive strategy of students is high, it does not contribute to the improvement of the ability of the students reading comprehension at SMAN 3 Curug in academic year 2019/2020. The research findings shows there is no correlation between metacognitive strategy and reading comprehension of students in SMAN 3 Curug. As the result, the value skills obtained by students was associated with the understanding of the low reading comprehension skills. These conditions also influenced in decreasing metacognitive strategy of the students, because they will feel hopeless with the result obtained. The findings of this research also have implications to the teachers, some efforts given to students by awarding something to students was useless. Therefore, the teachers are expected to try doing another approach to improve the student metacognitive strategy by praising or giving reward in order to appreciate what students done.